GEOGRAPHIC AND SOCIOECONOMIC DISPARITIES IN LONG-TERM MATERNAL MENTAL HEALTH OUTCOMES FOLLOWING OBSTETRIC COMPLICATIONS - Karimova Shohista; Eshnazarova Shaxzoda; Axtamova Nilufar Akbarjanovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Geographic and socioeconomic disparities exacerbate long-term maternal mental health issues post-obstetric complications, with rural and low-SES populations facing heightened risks of chronic depression, anxiety, and PTSD due to limited access to care and environmental stressors. This thesis analyzes recent data from diverse cohorts, revealing amplified vulnerabilities in underserved areas, including associations with heatwave exposures and neighborhood deprivation. Meta-analytic findings indicate odds ratios up to 2.5 for mental health disorders in low-SES groups, advocating for targeted interventions like telehealth and community-based programs to address inequities. The study emphasizes policy reforms to reduce barriers, potentially lowering incidence by 15-25% through equitable resource allocation.